Discussing the sexual consequences of treatment in radiotherapy and urology consultations with couples affected by prostate cancer - Forbat, Liz; White, Isabella; Marshall‐Lucette, Sylvie; Kelly, Daniel (BJU international, 2012)
Study Type – Attitude/patient experience analysis (retrospective cohort) Level of Evidence 2b What’s known on the subject? and What does the study add? Men with prostate cancer are likely to experience a range of treatment‐related side‐effects including deterioration in sexual functioning as a consequence of surgery, radiotherapy and hormone treatment. Despite the clear links between treatments and changes in sexual functioning, sexual concerns are infrequently discussed in clinic settings. Data indicate the need to use clinical consultations appropriately to support both patient and partner in sexual recovery and rehabilitation, going beyond discussions of assistive technologies to offer psychosexual couple support. OBJECTIVE • To explore the ways in which prostate cancer treatment‐induced sexual changes are presented as viable topics for discussion in urology and radiotherapy clinics. PATIENTS AND METHODS • Ethnographic observations were made of 60 consultations between clinicians, patients and partners in clinical oncology and prostate cancer urology clinics. RESULTS • Sexual functioning was discussed infrequently in both clinic settings. • Despite the presence of partners in nearly half of consultations, involvement of the partner tended to be minimal. • Overall, discussions of wider psychosexual concerns were marginalised in consultations, and there were limited opportunities for couples to discuss the specific impact of prostate cancer and its treatments on sexual functioning. CONCLUSION • Given the potential burden of symptoms and side‐effects, there is a need to include discussions of sexual recovery and rehabilitation in consultations, and to provide opportunities to discuss the sexual consequences of treatment with men and their partners